2015
DOI: 10.1001/jamaneurol.2015.0248
|View full text |Cite
|
Sign up to set email alerts
|

Use of Advanced Magnetic Resonance Imaging Techniques in Neuromyelitis Optica Spectrum Disorder

Abstract: Brain parenchymal lesions are frequently observed on conventional magnetic resonance imaging (MRI) scans of patients with neuromyelitis optica (NMO) spectrum disorder, but the specific morphological and temporal patterns distinguishing them unequivocally from lesions caused by other disorders have not been identified. This literature review summarizes the literature on advanced quantitative imaging measures reported for patients with NMO spectrum disorder, including proton MR spectroscopy, diffusion tensor ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 56 publications
(87 reference statements)
1
39
0
3
Order By: Relevance
“…Furthermore, brainstem lesions, cerebellar lesions, extensive WM lesions82 83 or cortical GM lesions84 are seen in some patients with NMO. Brain abnormalities on MRI are present in 60% of patients with NMO,82 and 5–42% of the patients fulfil the Barkhof criteria for MS 83 85…”
Section: Neurodegeneration In Nmomentioning
confidence: 99%
“…Furthermore, brainstem lesions, cerebellar lesions, extensive WM lesions82 83 or cortical GM lesions84 are seen in some patients with NMO. Brain abnormalities on MRI are present in 60% of patients with NMO,82 and 5–42% of the patients fulfil the Barkhof criteria for MS 83 85…”
Section: Neurodegeneration In Nmomentioning
confidence: 99%
“…More than 35.000 7.0 Tesla MR research examinations (1) have already been performed globally, producing valuable data that indicate the value of ultrahigh fields (2)(3)(4)(5)(6)(7)(8). Even if these instruments do not become standard tools in the everyday clinical setting in the very near future, the invaluable new insights they are providing into (patho)physiological processes will be helpful to patients everywhere.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Advanced MRI techniques may provide biomarkers that help the differential diagnosis. 6 Recent studies at 7T have shown that the presence of the central vein sign (CVS) within white matter lesions is a hallmark of MS and differentiates MS from NMOSD. [7][8][9] However, 7T scanners are not routinely available in the clinical setting.…”
mentioning
confidence: 99%